Increase in Toughness of 300-Grade Maraging Steel with Nb Addition - Gerardo Jesus Aracena Pérez; Angelo José Zimmermann; Isabel Ferreira Barros; Marcos Natan da Silva Lima; Edipo Silva; Luís Flávio Gaspar Herculano; Daniel Pallos Fridman; Alexandre Bellegard Farina; Miloslav Béreš; Mohammad Masoumi; Hamilton Ferreira Gomes de Abreu (Materials Research, 2025)
This study investigates the effect of niobium (Nb) addition on the microstructure and mechanical behavior particularly impact toughness of 300-grade maraging steel. Two novel Nb-modified alloys were developed: one with partial substitution of titanium (Ti) by Nb (0.64 wt.%), and another with complete substitution (1.4 wt.% Nb), based on a 1:2 Ti-to-Nb weight ratio. These were compared to a conventional 18Ni300 maraging steel. Thermodynamic and kinetic simulations using Thermo-Calc® and JMatPro® guided the alloy design, revealing that Nb addition favors the formation of Ni3Nb and Laves phases and delays precipitation kinetics compared to Ni3Ti. Microstructural characterization (XRD, SEM, EBSD) confirmed martensite refinement and reduced prior austenite grain size (PAGS) with increasing Nb content. Mechanical testing showed that the partially Nb-modified alloy exhibited the highest impact toughness, reaching 14.4 J, while maintaining a yield strength of 1.61 GPa and ultimate tensile strength (UTS) of 1.68 GPa. The fully Nb-substituted alloy achieved 13.4 J of impact toughness and recovered high strength levels (YS: 1.78 GPa, UTS: 1.83 GPa) comparable to commercial grades.